2013
DOI: 10.1515/caslar-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Production of formulaic expressions in L2 Chinese: A developmental investigation in a study abroad context

Abstract: This study investigated the development of L2 Chinese formulaic competence in a study abroad context. Participants were 31 American students studying Chinese in a university in China (intermediate-level). They completed a computerized speaking test consisting of 24 formulae-use situations twice during their semester-long study abroad in China. The learners produced a formulaic expression according to each situation, and their production was evaluated on appropriateness (rated on a four-point scale by native sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 35 publications
13
97
0
Order By: Relevance
“…As shown in table 2, gains in recognition of routines (5.73%) were slightly greater than those for production (5.27%), pointing to the particular advantage of the SA context in terms of recognition. These findings support previous research reporting that learners increase their knowledge of pragmatic routines while participating in SA programs (Barron 2003;Taguchi, Li and Xiao 2013).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in table 2, gains in recognition of routines (5.73%) were slightly greater than those for production (5.27%), pointing to the particular advantage of the SA context in terms of recognition. These findings support previous research reporting that learners increase their knowledge of pragmatic routines while participating in SA programs (Barron 2003;Taguchi, Li and Xiao 2013).…”
Section: Resultssupporting
confidence: 91%
“…While the above-mentioned studies are cross-sectional, measuring knowledge and performance of pragmatic routines while abroad, Barron (2003) and Taguchi, Li and Xiao (2013) addressed actual gains in pragmatic routines during SA, focusing on production. Barron (2003) examined the acquisition of discourse structure, pragmatic routines and internal modification by thirty-three Irish students of L2 German in a tenmonth SA program in Germany.…”
Section: Previous Research On the Acquisition Of Pragmatic Routinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoffman-Hicks' (1999) longitudinal study only a few investigations have traced the development of L2 learners' pragmatic competence longitudinally (Ren, 2015;Schauer, 2006, Woodfield, 2012see Xiao, 2015, for a review on longitudinal studies of pragmatic development), and even fewer studies have focused on pragmatic routines (Barron, 2003;Taguchi et al, 2013). These investigations report the benefits of SA for the acquisition of pragmatic routines.…”
Section: Study Abroad Exposure and Pragmatic Routinesmentioning
confidence: 99%
“…conclusions have been reached in 3 areas: studies that have revealed a significant effect of length of stay on the acquisition of routines (Roever, 2005(Roever, , 2011Roever, Wang & Brophy, 2014), studies that have reported no significant effect of amount of time spent abroad on pragmatic acquisition (Bardovi-Harlig & Bastos, 2011;Kecskes, 2000), and studies that have observed some positive effect, although they have claimed that length of stay does not determine reaching full native-like pragmatic performance (Barron, 2003;Taguchi et al, 2013). In the three cases, intensity of interaction, understood as quantity and quality of interactions with L2 users, had a positive influence on the acquisition of pragmatic routines.…”
Section: Study Abroad Exposure and Pragmatic Routinesmentioning
confidence: 99%